2020
DOI: 10.1002/jso.26092
|View full text |Cite
|
Sign up to set email alerts
|

Management of orthopedic oncology patients during coronavirus pandemic

Abstract: The new measures implemented in hospitals also altered the operation of orthopedics and traumatology departments. The main purpose of this article is to discuss how orthopedic oncology clinics should be organized during the pandemic and to present the process management scheme for patients requiring orthopedic surgery, including trauma surgery, from diagnosis to treatment, together with our experiences. Instead of thinking about the global emergence of the epidemic, it is time to act decisively. At first glanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
0
13
0
2
Order By: Relevance
“…However, as the duration of the pandemic is longer than expected, the treatment of patients other than fracture remains a concern in the orthopedic practice. Some authors [33][34][35] have suggested that new treatment guidelines should be created during the pandemic period for different subspecialties, such as pediatric orthopedics, orthopedic oncology, and shoulder and elbow surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the duration of the pandemic is longer than expected, the treatment of patients other than fracture remains a concern in the orthopedic practice. Some authors [33][34][35] have suggested that new treatment guidelines should be created during the pandemic period for different subspecialties, such as pediatric orthopedics, orthopedic oncology, and shoulder and elbow surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Preserving orthopaedic services during the COVID‐19 pandemic has been challenging internationally 3,4 . Trauma, spinal emergencies and urgent orthopaedic oncology have continued during the pandemic, and recent landmark studies have reported 30‐day mortality rates of 28.8% in orthopaedic patients 1 .…”
Section: Discussionmentioning
confidence: 99%
“…При метастатическом поражении позвоночника хирургическое лечение зачастую проводится по жизненным показаниям, так как нарастающая компрессия спинного мозга становится причиной развития плегии. Наличие у пациента патологического перелома длинных костей также является показанием к проведению экстренного хирургического лечения [3,4]. В исследовании J. Stevenson и соавт.…”
Section: Discussionunclassified